RESPONSE OF DIFFERENT CONCENTRATIONS OF UREA, KNO3 AND MICRONUTRIENT MIXTURE ON QUALITY OF SAPOTA (MANILKARA ACHRAS (MILL.) FOSBERG) CV. KALIPATTI - J. J. AMARCHOLI; S. MOMIN, K. M. SHARMA, V. SINGH, (The Bioscan, 2016)
In sapota a peak season harvesting always result in market glut and thus reduction in prices. For sustenance in non-peak season an experiment was conducted during the year 2013-14 at College Farm, College of Agriculture, Navsari Agricultural University, Bharuch Campus, Bharuch (Gujarat) to get quality yield. The experiment was laid out with ten treatments in Randomized Block Design and replicated three times. The treatment comprised of three different concentrations of Urea (T1: 1 %, T2: 1.5 % and T3: 2 %), KNO3 (T4: 1%, T5: 1.5 % and T6: 2 %), Micronutrient Mixture Grade-4 (T7: 1 %, T8: 1.5 % and T9: 2 %) along with control as water spray (T10). All the chemicals were sprayed twice: first in the month of November at the marble stage and second in the month of January. Among the quality parameters T9 was found superior with fruit firmness (0.56 kg cm-2), TSS (21.36o Brix), acidity (0.199 %), ascorbic acid(19.17 mg 100g-1), total sugar (17.41 %), reducing sugar (9.86 %) and nonreducing sugar (7.55 %) which is found at par with T8